Psychometric evaluation of the characteristics of resilience in sports team inventory in China - Yang, Y.; Li, Y.; Sun, Y. (PLOS ONE, 2020)
This study examines the reliability and validity of the Characteristics of Resilience in Sports Teams Inventory (CREST) in Chinese team athletes. A sample of 659 athletes (male = 355, female = 304) aged from 16-34 (M = 20.08, SD = 2.98) participated in this study. The scale was translated into Chinese using forward and back translation procedures by two independent translators. Questionnaires were administered online. Data was analysed using SPSS 19.0 and Mplus 6.0. Results showed that the items were understood by Chinese team sport athletes. Exploratory factor analysis showed that the Chinese version of CREST had two sub-dimensions as it was in the original scale. Confirmatory factor analysis further demonstrated that the two-structure model was confirmed in the Chinese team sports context. The Cronbach`s alpha values of the scale was 0.842, and the test-retest reliability coefficient of one-month interval was 0.836. It is concluded that the Chinese version of CREST can be used as a valid and reliable tool to assess team resilience in China and can be helpful and applicable in helping sports psychologists understand team resilience. Future studies should further examine the psychometric properties of the scale among world-class athletes and develop a team resilience measurement tool based on Chinese traditional culture.